CONDITION OF CORAL AND REEF FISH IN THE LOCATION OF FISH CATCHING USING DYNAMITE FISHING IN KAPOPOSANG WATER PARK AND THE SURROUNDING SEA - Mahmudin, Mahmudin; Rani, Chair; Hamzah, Hamzah (Hasanuddin University, 2020)
Dynamite fishing is one of the causes of damage to the coral reef ecosystem in Indonesia. Fishing activities using explosives (dynamite fishing) occur because of the desire of fishermen to get a lot of catch with low cost in a short time. Kapoposang Water Park (WP) is a region rich in marine biological resources. However, dynamite fishing activities which are still found within the area have caused the coral reef ecosystem to be severely damaged. The results showed a lower difference in the percentage of live coral cover at dynamite fishing locations (DF1, DF2) compared to control locations (K1, K2). In addition, the highest average values of coral fish abundance were found at locations K1, DF1, and DF2. Conversely, the results of the analysis found the lowest fish abundance at the K2 location. Different from the average number of reef fish species that were higher at the control location (K1, K2) compared to dynamite fishing locations (DF1, DF2). For the target fish biomass there is no real difference between the control location and dynamite fishing.